RESEARCH ON INVOLVEMENT EXTRAVERT AND INTROVERT TYPES IN SOCIAL NETWORKS - Khachatryan, А.S. (Modern Psychology, 2021)
The article discusses the current active role of social networks, as well as the general orientation types, extraversion and introversion peculiarities. The results of the pilot survey, the relationship between the involvement of the individual in social networks and extrovert, introvert users summarized.
Keywords: internet, social networks, extraversion, introversion, ambivercity.